Taxonomic review of the Tribe Melaenini (Coleoptera: Carabidae), with observations on morphological, ecological and chorological evolution - Ball, George E.; Shpeley, Danny (Zootaxa, 2005)
A taxonomic review of the tribe Melaenini (sensu novo), this paper includes a classification, keys at all taxonomic levels, descriptions (tribe to species), re-rankings, and new synonymy. In total, two genera and 22 species (three of which are new) are treated. Arrangement of taxa is in the following sequence, with junior synonyms and type localities of new species in parentheses, following name of the taxon. The Eastern Hemisphere genus Melaenus Dejean, 1831 includes M. piger (Fabricius, 1801), and M. elegans Dejean, 1831 (with M. elongatus Chaudoir, 1843, as a new junior synonym), which exhibits marked dimorphism in East Africa. The genus Cymbionotum Baudi di Selve, 1864 includes 20 species, arranged in two subgenera, as follows. The Western Hemisphere Procoscinia, n. subg. (type species, C. fernandezi, n. sp. [Zambrano, Bolivar, Colombia]), includes the type species and C. negrei Perrault, 1994. The Eastern Hemisphere subgenus Cymbionotum (sensu stricto) includes 18 species in three species groups, and three superspecies. The basale species group includes two species: C. semirubricum (Reitter, 1914) (new junior synonyms Graniger aethiopicus Alluaud, 1923, C. minax Andrewes, 1935, and C. a. airense Basilewsky, 1950), and C. basale (Dejean, 1831). The semelederi species group includes three species: C. semelederi (Chaudoir, 1851) (new junior synonyms, Coscinia funerula Fairmaire, 1885, Cymbionotum luniferum Andrewes 1935, and Graniger houskai Jedli…ka, 1951), C. striatum Reitter, 1894, and C. mandli Jedli…ka, 1963.